How to Think about Remedies in the Generative AI Copyright Cases. - Samuelson, Pamela (Communications of the ACM, 2024)
The article focuses on the possible remedies in the generative artificial intelligence (AI) copyright cases that have been filed against OpenAI and other developers. The author discusses the claims for awards of statutory damages as authored under U.S. law, the violation of copyright management information (CMI), and the four complaints that explicitly ask courts to order generative AI defendants to destroy the models that were trained on their works.